2022
DOI: 10.1155/2022/6384334
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Ginkgolide A Participates in LPS‐Induced PMVEC Injury by Regulating miR‐224 and Inhibiting p21 in a Targeted Manner

Abstract: Most studies have focused on the protective effects of ginkgolide A against ischemia/reperfusion-induced cardiomyopathy and injury of the brain, liver, and other organs, but there are few reports about the protection of lung tissues. This study was designed to clarify the protection of ginkgolide A against lipopolysaccharide (LPS)-induced pulmonary microvascular endothelial cell (PMVEC) injury. PMVECs were extracted and fell into control, LPS, and ginkgolide A groups. Next, we delved into the growth activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The Ginkgo extract favors thrombomodulin (TM) expression and t-PA secretion contributing to the protection of the endothelium in the procoagulant and prothrombotic phases (observations by assay on HUVEC cells) [ 35 ]. Ginkgolide A demonstrated antiapoptotic effects by modulating the expression of miR-224 and regulating the expression of p21 at the endothelial level (PMVEC—pulmonary microvascular endothelial cells) [ 36 ]. Ginkgolide B has an anti-inflammatory effect observed on HUVEC cells by downregulating LOX-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The Ginkgo extract favors thrombomodulin (TM) expression and t-PA secretion contributing to the protection of the endothelium in the procoagulant and prothrombotic phases (observations by assay on HUVEC cells) [ 35 ]. Ginkgolide A demonstrated antiapoptotic effects by modulating the expression of miR-224 and regulating the expression of p21 at the endothelial level (PMVEC—pulmonary microvascular endothelial cells) [ 36 ]. Ginkgolide B has an anti-inflammatory effect observed on HUVEC cells by downregulating LOX-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%